Implementasi Kurikulum 2013 Pada Pembelajaran Akidah Akhlak Kelas X di Madrasah Aliyah Negeri 1 Pekanbaru - Suparman Suparman (Milenial: Journal for Teachers and Learning, 2022)
This study aims to determine how the implementation of the 2013 curriculum in Akidah Akhlak lesson in class X Madrasah Aliyah Negeri 1 Pekanbaru. The type of research used in field research using descriptive analysis methods. The research data was taken using triangulation techniques, namely the results of observations, interviews, and documentation. The result of this study stated that at MAN 1 Pekanbaru had implemented Akidah Akhlak learning according to the 2013 curriculum using a student-centered scientific approach. In the planning stage, the teachers prepare learning tools based on the 2013 curriculum. While the learning evaluation activities use authentic assessments according to the 2013 curriculum. The assessment is caried out on 3 aspects, namely the assessment of attitudes, knowledge, and skills.